Ответ: x ∈ (-1.5; -1).
Пошаговое объяснение:
-1 < 2x + 2 < 0 |-2
-1 - 2 < 2x + 2 - 2 < 0 - 2
-3 < 2x < -2 |:2
-3/2 < x < -1
x ∈ (-1.5; -1).
8,2 **************************************
ОДЗ
3x+10≥0
3x≥-10
x≥-3 1/3
x∈[-3 1/3;∞)
[x²-2=0
[2^(x-1)-2^(√(3x+10)-2)=0
1)x²-1=0
x²=1
x=-1 U x=1
2)2^(x-2)-2^(√3x+10)-2)=0
2^(x-2)=2^(√(3x+10)-2)
x-2=√(3x+10)-2
x=√(3x+10)
возведем в квадрат
x²=3x+10
x²-3x-10=0
x1+x2=3 U x1*x2=-10
x1=5
x2=-2
Ответ x={-2;-1;1;5}
0,25=1/4=4^(-1) ; 64=4^3
4^(-1)*(4x+3)=4^3
т.к. основания одинаковые
-4x - 3 = 3
-4x = 6
x = -6/4
x = -1,5